The age of lone wolf terrorism - Hamm, Mark S.; Spaaij, R. F. J. (Ramon F. J.) (Studies in transgression., 2017)
The lethality of lone-wolf terrorism has reached an all-time high in the United States. Isolated individuals using firearms with high-capacity magazines are committing brutally efficient killings with the aim of terrorizing others, yet there is little consensus on what connects these crimes and the motivations behind them. In The Age of Lone Wolf Terrorism, terrorism experts Mark S. Hamm and Ramón Spaaij combine criminological theory with empirical and ethnographic research to map the pathways of lone-wolf radicalization, helping with the identification of suspected behaviors and recognizing patterns of indoctrination. Reviewing comprehensive data on these actors, including more than two hundred terrorist incidents, Hamm and Spaaij find that a combination of personal and political grievances lead lone wolves to befriend online sympathizers--whether jihadists, white supremacists, or other antigovernment extremists--and then announce their intent to commit terror when triggered. Hamm and Spaaij carefully distinguish between lone wolves and individuals radicalized within a group dynamic. This important difference is what makes this book such a significant manual for professionals seeking richer insight into the transformation of alienated individuals into armed warriors. Hamm and Spaaij conclude with an analysis of recent FBI sting operations designed to prevent lone-wolf terrorism in the United States, describing who gets targeted, strategies for luring suspects, and the ethics of arresting and prosecuting citizens.